PIRING MAKAN KU “MAKAN SEHAT UNTUK TUMBUH KEMBANG ANAK” - Ismiy Wahyuni; Indra Fauzi Sabban; Siska Kusuma Wardani; Rizal Aditya Hermawan; Fathul Hidayatul Hasanah; Sri Wahyuni; Moch. Abdul Rokim; Jessi Suryani Setiawan (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
It is hoped that the healthy eating pattern approach will not be carried out with angry or violent actions but rather with a good approach so that children can enjoy eating and support their growth and development. An approach that can be taken to encourage children to consume healthy food is introducing various types of food and their contents as a basis for children's knowledge. With this knowledge, children can assess whether the food content on their dinner plate includes four healthy, five perfect, or not. Based on this, it is important to carry out Community Service (PkM) activities targeting elementary school students at SDN Karanganyar Village, Wates District, Kediri Regency. This PkM activity aims to invite students to become familiar with the contents of foods that are often found in the daily diet as an effort to maintain a healthy diet for children's growth and development. Based on the observations and evaluations, the students were enthusiastic when receiving material about "My Dinner Plate" and guessing the nutritional content of various foods. The results of the T-test show a value of 0.001, which means there is a significant difference between the pre-test and post-test scores and there is an increase in students' knowledge of 70%.